Age-specific prevalence and years of healthy life in a system with three health states. - Diehr, Paula; Yanez, David; Derleth, Ann; Newman, Anne B (Stat Med, 2008)
Consider a 3-state system with one absorbing state, such as Healthy, Sick, and Dead. Over time, the prevalence of the Healthy state will approach an 'equilibrium' value that is independent of the initial conditions. We derived this equilibrium prevalence (Prev:Equil) as a function of the local transition probabilities. We then used Prev:Equil to estimate the expected number of years spent in the healthy state over time. This estimate is similar to the one calculated by multi-state life table methods, and has the advantage of having an associated standard error. In longitudinal data for older adults, the standard error was accurate when a valid survival table was known from other sources, or when the available data set was sufficient to estimate survival accurately. Performance was better with fewer waves of data. If validated in other situations, these estimates of prevalence and years of healthy life (YHL) and their standard errors may be useful when the goal is to compare YHL for different populations.
Keywords: Age Factors; Biometry; Health Status; Humans; Life Tables; Longitudinal Studies; Middle Aged; Models, Statistical; Probability; Quality-Adjusted Life Years